2018
DOI: 10.1167/iovs.17-23498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automatically Quantified Foveal Avascular Zone Metrics for Diagnosis of Diabetic Retinopathy Using Optical Coherence Tomography Angiography

Abstract: PurposeTo describe an automated algorithm to quantify the foveal avascular zone (FAZ), using optical coherence tomography angiography (OCTA), and to compare its performance for diagnosis of diabetic retinopathy (DR) and association with best-corrected visual acuity (BCVA) to that of extrafoveal avascular area (EAA).MethodsWe obtained 3 × 3-mm macular OCTA scans in diabetic patients with various levels of DR and healthy controls. An algorithm based on a generalized gradient vector flow (GGVF) snake model detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 45 publications
2
86
2
2
Order By: Relevance
“…Table 2 Segmentation performance of the proposed method in each parameter group Parameter group Dice similarity coefficient (mean ± SD) Sensitivity (mean ± SD) Specificity (mean ± SD) R G1 0.977 ± 0.001 0.972 ± 0.017 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G2 0.975 ± 0.011 0.967 ± 0.022 0.999 ± 0.001 0.997 (p = 0.000 < 0.5) G3 0.977 ± 0.001 0.972 ± 0.017 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G4 0.976 ± 0.010 0.972 ± 0.018 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G5 0.976 ± 0.010 0.972 ± 0.018 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G6 0.976 ± 0.010 0.973 ± 0.018 0.999 ± 0.001 0.997 (p = 0.000 < 0.5) G7 0.977 ± 0.009 0.974 ± 0.016 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G8 0.975 ± 0.011 0.971 ± 0.020 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G9 0.972 ± 0.013 0.975 ± 0.018 0.999 ± 0.001 0.996 (p = 0.000 < 0.5) Table 3 Comparison of the segmentation performance between our proposed method and similar studies Study Dice similarity coefficient R Lu et al . [12] 0.808 0.792 (p = 0.000 < 0.5)…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Table 2 Segmentation performance of the proposed method in each parameter group Parameter group Dice similarity coefficient (mean ± SD) Sensitivity (mean ± SD) Specificity (mean ± SD) R G1 0.977 ± 0.001 0.972 ± 0.017 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G2 0.975 ± 0.011 0.967 ± 0.022 0.999 ± 0.001 0.997 (p = 0.000 < 0.5) G3 0.977 ± 0.001 0.972 ± 0.017 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G4 0.976 ± 0.010 0.972 ± 0.018 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G5 0.976 ± 0.010 0.972 ± 0.018 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G6 0.976 ± 0.010 0.973 ± 0.018 0.999 ± 0.001 0.997 (p = 0.000 < 0.5) G7 0.977 ± 0.009 0.974 ± 0.016 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G8 0.975 ± 0.011 0.971 ± 0.020 0.999 ± 0.001 0.998 (p = 0.000 < 0.5) G9 0.972 ± 0.013 0.975 ± 0.018 0.999 ± 0.001 0.996 (p = 0.000 < 0.5) Table 3 Comparison of the segmentation performance between our proposed method and similar studies Study Dice similarity coefficient R Lu et al . [12] 0.808 0.792 (p = 0.000 < 0.5)…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, Lu et al [12] extracted an sFAZ by applying a region-growing approach, in which the image center point was manually selected as a seed. The final sFAZ segmentation result was obtained by applying morphological operators and an active contour model.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Studies also showed the clinical applicability of OCTA for diagnosis and management of glaucoma, and retinal and choroidal diseases. 5,[15][16][17][18][19][20] However, these were hospital-based studies with relatively few subjects and potential selection bias. A population-based, rather than a hospital-based, investigation has the advantage of being free of potential selection bias induced by referring doctors.…”
mentioning
confidence: 99%
“…Therefore, further studies with a larger scan area are needed. Third, several studies have already shown that systemic diseases, including diabetes, contribute to a macular VD decrease and an increase in the foveal avascular zone area [44][45][46] . However, an ADRVD was not detected in any of the examined patients with diabetes.…”
Section: Discussionmentioning
confidence: 98%